Study of Osteopontin as the “CA125” Adjunct for Detection of Ovarian Carcinoma in Patients with Pelvic Mass - Shahidsales, Soodabeh; Hasanzadeh, Malihe; Ayatollahi, Hossein; Shirinzadeh, Laya (Reports of Radiotherapy and Oncology, 2024)
No Abstract